Surgical: Resection/Destructive Procedures - Sharma, Akshay; Serletis, Demitre; Gupta, Ajay (Seminars in Neurology, 2025)
Surgical resection and ablation are powerful tools in the treatment of medically refractory epilepsy. In this study, we review a broad array of resective and ablative procedures available to the epilepsy surgeon to address surgical epileptic disease. Here, we aim to provide a brief overview of a very broad category of treatments to provide a better understanding of the breadth of treatments available to providers and patients.
Keywords: epilepsy surgery; resection; lobectomy; ablation